2020
DOI: 10.1071/mf19231
|View full text |Cite
|
Sign up to set email alerts
|

Using optimised otolith sectioning to determine the age, growth and age at sexual maturity of the herbivorous fish Kyphosus bigibbus: with a comparison to using scales

Abstract: Determining the population parameters of herbivorous fishes facilitates our understanding of their overall effects on ecosystems. However, this has not been successful with species such as Kyphosus bigibbus that are difficult to age using otoliths. In this study, we estimated the age, growth and age at sexual maturity of K. bigibbus off the west coast of Kyushu, Japan, using fish scales and otoliths. Scales were found unreliable because they caused underestimation of the age of fish older than 5 years, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Two other kyphosids, the silver, Scorpis lineolata , and sea, S. aequipinnis , sweeps are both long‐lived (maximum ages of 54 and 78 years, respectively) and are highly susceptible to localized depletion (Coulson et al ., 2012; Stewart & Hughes, 2005). The only available age estimates for a Kyphosus species, grey drummer, K. bigibbus , indicate that this species attains ages of at least 46 years (Ogino et al ., 2020) whereas preliminary age estimates for K. sydneyanus suggest that this species can attain ages >90 years (P.C. Coulson unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Two other kyphosids, the silver, Scorpis lineolata , and sea, S. aequipinnis , sweeps are both long‐lived (maximum ages of 54 and 78 years, respectively) and are highly susceptible to localized depletion (Coulson et al ., 2012; Stewart & Hughes, 2005). The only available age estimates for a Kyphosus species, grey drummer, K. bigibbus , indicate that this species attains ages of at least 46 years (Ogino et al ., 2020) whereas preliminary age estimates for K. sydneyanus suggest that this species can attain ages >90 years (P.C. Coulson unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…While no evidence of spawning or settlement of juveniles has been documented, K . biggibus has become more abundant in recent decades in Japan and can live up to 46 years (Ogino et al., 2020). The available reports about the recruitment of other species of kyphosids indicate an association of juveniles with shallow reefs (Moran & Clements, 2002; Rimmer, 1986; Silvano & Güth, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although Garrett (1997) suggested that otoliths of E. tetradactylum be sectioned prior to reading, Pember et al (2005) found that sectioning did not improve the accuracy of age estimation in this species. In this study, to determine whether otolith sectioning was useful, otoliths of 72 specimens were sectioned transversely following the method described by Ogino et al (2020) and investigated under a stereoscopic microscope.…”
Section: Otolith Macrostructurementioning
confidence: 99%